A 16th century Italo-Byzantine cross (Piscataway, NJ)
xi, 169 sayfa
Keywords: “The contributors have tried to reconstruct the mingling of two cultures, Greek and Italian, in sixteenth century Venice. This is examined through the medium of a single intricately carved wooden cross, executed by a Greek carver, with adaptations suitable to a member of the Latin church. We can identify the carver who made the cross and make some speculations about his life, and how he and his art are reflective of this hybrid culture. This type of cross seems to be for personal, rather than liturgical use, and it seems to be intended for private meditation on the Passion“ -- Yayıncı.